2016
DOI: 10.1016/j.jth.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Changes in bicycling over time associated with a new bike lane: Relations with kilocalories energy expenditure and body mass index

Abstract: Although bicycling has been related to positive health indicators, few studies examine health-related measures associated with non-competitive community cycling before and after cycling infrastructure improvements. This study examined cycling changes in a neighborhood receiving a bike lane, light rail, and other “complete street” improvements. Participants wore accelerometers and global positioning system (GPS) data loggers for one week in both 2012 and 2013, pre- and post- construction completion. Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Empirical studies included in the review were published between 2005 and 2017 ( Table 3 ). These studies were based in: North America, including the United States (n = 11) ( Boarnet et al, 2005 ; Evenson et al, 2005 ; Burbidge and Goulias, 2009 ; Parker et al, 2011 ; Chen et al, 2012 ; Parker et al, 2013 ; Dill et al, 2014 ; Brown et al, 2016 ; Cook et al, 2016 ; Ferenchak and Marshall, 2016 ; Brown et al, 2016b ) and Canada (n = 1) ( Bhatia et al, 2016 ); Europe, specifically, the United Kingdom (n = 9) ( Goodman et al, 2013 ; Goodman et al 2013b ; Goodman et al 2014 ; Heinen et al, 2015 ; Panter and Ogilvie, 2015 ; Heinen and Ogilvie, 2016 ; Panter et al, 2016 ; Panter and Ogilvie, 2017 ; Song et al, 2017 ) and Denmark (n = 1) ( Jensen, 2008 ); and Australia (n = 4) ( Greaves et al, 2015 ; Langdon, 2015 ; Rissel et al, 2015 ; Heesch et al, 2016 ). Only three studies were based in LMIC, specifically, Colombia, Mexico and Brazil ( Cerdá et al, 2012 ; Pazin et al, 2016 ; Chang et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Empirical studies included in the review were published between 2005 and 2017 ( Table 3 ). These studies were based in: North America, including the United States (n = 11) ( Boarnet et al, 2005 ; Evenson et al, 2005 ; Burbidge and Goulias, 2009 ; Parker et al, 2011 ; Chen et al, 2012 ; Parker et al, 2013 ; Dill et al, 2014 ; Brown et al, 2016 ; Cook et al, 2016 ; Ferenchak and Marshall, 2016 ; Brown et al, 2016b ) and Canada (n = 1) ( Bhatia et al, 2016 ); Europe, specifically, the United Kingdom (n = 9) ( Goodman et al, 2013 ; Goodman et al 2013b ; Goodman et al 2014 ; Heinen et al, 2015 ; Panter and Ogilvie, 2015 ; Heinen and Ogilvie, 2016 ; Panter et al, 2016 ; Panter and Ogilvie, 2017 ; Song et al, 2017 ) and Denmark (n = 1) ( Jensen, 2008 ); and Australia (n = 4) ( Greaves et al, 2015 ; Langdon, 2015 ; Rissel et al, 2015 ; Heesch et al, 2016 ). Only three studies were based in LMIC, specifically, Colombia, Mexico and Brazil ( Cerdá et al, 2012 ; Pazin et al, 2016 ; Chang et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among these, one study evaluated newly built aerial tram infrastructure which was implemented in combination with other neighborhood improvements including, additional lighting in public spaces, pedestrian bridges and recreational centers ( Cerdá et al, 2012 ). Five studies evaluated the health effects of bicycle lanes which were variously combined with a host of interventions such as light rail and pedestrian infrastructure improvements, the creation of parking facilities and additional lighting ( Boarnet et al, 2005 ; Goodman et al, 2013 ; Brown et al, 2016 ; Pazin et al, 2016 ; Brown et al, 2016b ). The remaining studies (n = 4) combined BRT and bicycle/pedestrian paths with park-and-ride sites ( Heinen et al, 2015 ; Heinen and Ogilvie, 2016 ; Panter et al, 2016 ; Chang et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A pollution focused study in Colorado USA made 45 participants travelling with all modes to wear a modified backpack containing GPS together with air intake tubes connected to air quality instrumentation [ 46 ]. Lastly two before and after infrastructure evaluation studies in Portland [ 47 ] and Salt Lake City, USA [ 48 ] required 341 and 939 participants respectively to wear both a GPS device and accelerometer.…”
Section: Resultsmentioning
confidence: 99%
“…Diffusion of Innovation also categorises individuals into stages reflecting their readiness to change. Heesch et al (2016) and Brown et al (2016) have taken advantage of 'natural experiments' (Craig et al, 2012) to study the effects of new bicycle infrastructure. Heesch and colleagues found that a new veloway can increase distances cycled.…”
mentioning
confidence: 99%